Political constraints and opportunities for agricultural investment in Sudan - D'Silva, Brian; Hassan, Rashid; Hutur, Abdelrahman; Ibrahim, Sami; Abushama, Hala; Siddig, Khalid; Kirui, Oliver K. (International Food Policy Research Institute, 2023)
This note reviews Sudan’s contemporary political landscape and how it affects the viability of much needed investments central to the country’s agricultural transformation. It specifically focuses on livestock and horticulture value chains in Greater Khartoum and natural resource management in the Blue Nile and South Kordofan States. Successive governments have largely neglected the agriculture sector even though it is the largest employment sector in Sudan and contributes about 56 percent to total exports (CBoS, 2020). Moreover, the sector has a high potential for tackling the twin challenges of food insecurity and improving the livelihoods of smallholder farmers. These two are critical priorities given high food price inflation and restricted access to agricultural inputs exacerbated by the Ukraine war. An enabling political and governance environment is essential for adopting and implementing the policies required for agricultural transformation, especially in fragile states like Sudan. This Political Economy Assessment (PEA) exercise has highlighted that the military and paramilitary structures occupy a large market share of the State-Owned Enterprises (SOEs), private company partnerships, and land leases to foreign companies in the agriculture sector. Thus, this study forms a basis for deeper PEA and an opportunity for the exploration of the role of intermediaries and the rent seeking activities at the subsequent levels of agricultural value chains, and the extent to which they are linked to both formal and informal economic structures. We have highlighted how smallholder farmers are largely disadvantaged given the current distribution of economic rents.